Analysis of Zakat Distribution Patterns of National Zakat Collection Institutions - Aisa Arif; Nurul Khatimah; Waode Zehan Masyita (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study aims to analyze the distribution patterns of zakat in Indonesia using an Islamic Statistics approach as the analytical framework. Islamic Statistics is understood as a quantitative method grounded in Sharia values, particularly emphasizing justice and public welfare. The data were obtained from the annual reports of national zakat management organizations (BAZNAS and Dompet Dhuafa) for the period 2020–2023 and analyzed using descriptive statistical methods. The results show that zakat distribution remains concentrated on two primary asnaf categories the destitute and the poor with most funds allocated to the Greater Jakarta area (Jabodetabek). In contrast, the eastern regions of Indonesia and other asnaf categories, such as riqab and ibnu sabil, receive minimal attention. This imbalance indicates the need for a more equitable, data-driven zakat distribution system. The Islamic Statistics approach presented in this study offers a new perspective for more just and effective zakat distribution decision-making. These findings serve as a foundation for the future development of digital zakat management systems based on maqashid shariah principles